Facing Ethical Dilemmas as Professional Accountants in the Future: Do They Aware? - Ferry Diyanti; Hariman Bone; Mega Norsita; Eka Febriani; Puspita Ningsih (Journal of International Conference Proceedings (JICP), 2022)
Accountants often face ethical dilemmas, so appropriate ethical decisions and actions are needed. Accounting students must be able to identify ethical dilemmas. This study aims to get an overview of the ability of accounting students to identify the ethical dilemmas faced. This research uses an exploratory method through an in-depth interview with internship accounting students in government and private institutions. The results showed that students currently participating in the internship program could feel and identify ethical dilemmas in their work. They can identify the procurement of equipment and services used for personal purposes,  empty notes, and the fraudulent in preparation of financial statements. However, factors of superior pressure, position in work, work environment and organizational culture force them to remain silent and or carry out the ethical dilemma practices they face. These results show that business ethics learning methods have not been able to encourage interns to make decisions and take ethical actions. Keywords: Accounting Students, Ethical Decisions and Actions, Ethical Dilemmas, Moral Awareness, Internships.